Chlorophyll f synthesis by a super-rogue photosystem II complex - Trinugroho, Joko P; Bečková, Martina; Shao, Shengxi; Yu, Jianfeng; Zhao, Ziyu; Murray, James W; Sobotka, Roman; Komenda, Josef; Nixon, Peter J (Nature plants, 2020)
Certain cyanobacteria synthesize chlorophyll molecules (Chl d and Chl f) that absorb in the far-red region of the solar spectrum, thereby extending the spectral range of photosynthetically active radiation1,2. The synthesis and introduction of these far-red chlorophylls into the photosynthetic apparatus of plants might improve the efficiency of oxygenic photosynthesis, especially in far-red enriched environments, such as in the lower regions of the canopy3. Production of Chl f requires the ChlF subunit, also known as PsbA4 (ref. 4) or super-rogue D1 (ref. 5), a paralogue of the D1 subunit of photosystem II (PSII) which, together with D2, bind cofactors involved in the light-driven oxidation of water. Current ideas suggest that ChlF oxidizes Chl a to Chl f in a homodimeric ChlF reaction centre (RC) complex and represents a missing link in the evolution of the heterodimeric D1/D2 RC of PSII (refs. 4,6). However, unambiguous biochemical support for this proposal is lacking. Here, we show that ChlF can substitute for D1 to form modified PSII complexes capable of producing Chl f. Remarkably, mutation of just two residues in D1 converts oxygen-evolving PSII into a Chl f synthase. Overall, we have identified a new class of PSII complex, which we term 'super-rogue' PSII, with an unexpected role in pigment biosynthesis rather than water oxidation.
Keywords: chlorofyl; geneticky modifikované mikroorganismy; sekvenční analýza proteinů; Microorganisms, Genetically-Modified; Synechocystis; Sequence Analysis, Protein; fotosystém II (proteinový komplex); sinice; Cyanobacteria; Chlorophyll; Photosystem II Protein Complex